PRODUKSI BIOKOMPOSIT DARI RUMPUT GAJAH (PENNISETUM PURPUREUM) HASIL FITOREMEDIASI LIMBAH DENGAN KANDUNGAN KROMIUM MELALUI FERMENTASI FASE PADAT OLEH JAMUR LINGZHI (GANODERMA LUCIDUM) - Lumongga Hugo Sianturi, Natasha
Integration of phytoremediation and biomaterial production is a promising strategy. It can offer advantages such as waste management systems and lignocellulosic residues valorization. The general objectives of this study were to: (1) determine the tolerance capacity and phytoremediation effectivity by Napier grass at 20 ppm Cr(VI), 40 ppm Cr(VI), and tannery wastewater (2) evaluate mycelium growth and biocomposite by Ganoderma lucidum at Napier grass from phytoremediation and inoculum percentage variations. P. purpureum was grown in a Horizontal Subsurface Flow Constructed Wetland with the size of 75x40x40 cm3 using a batch system for 31 days. P. purpureum from phytoremediation was used as solid-state fermentation (SSF) substrate. SSF was carried out in two stages (i.e., SSF 1 in plastic, SSF 2 in mold). The results showed that P. purpureum can tolerate all treatments as indicated by dry biomass and relative growth. The phytoremediation of Cr by P. purpureum was effective as indicated by characteristics of the medium (BOD, COD, pH, and TDS). The removal capacity of the plant to total Cr and Cr(VI) was varied from 71.79% to 99.96% and 99.95% to 99.96%. The plant's ability to accumulate Cr in its roots was shown by its translocation factor (TF) < 1, which indicated its capacity as a phytoremediator for Cr. G. lucidum growth was significantly affected by inoculum percentage. G. lucidum growth was not significantly affected by P. purpureum from phytoremediation. These results showed that G. lucidum showed a good tolerance to Cr in substrate. The final length and colonization G. lucidum varied in the range of 5.91–18.73 mm and 2–5 respectively. The water content of the final SSF substrate varied in the range of 46.55–53.40%. The biocomposite density varied in the range of 0.224?0.257 g/cm3. Moisture content in biocomposite varied in the range of 7.06?8.57%. Water absorption of biocomposite varied in the range of 73.84-304.58%. The characteristics of the biocomposite produced in this study have a good potential to be applied in agriculture as plant seedlings.